PEMBAGIAN KERJA DALAM KELUARGA DIFABEL MUSLIM: TINJAUAN SOSIOLOGI KELUARGA TERHADAP DIFABEL DI KELURAHAN COMONGAN, KABUPATEN SUKOHARJO, JAWA TENGAH - Kresna Wahyu Nugraha; Adib Sofia (IAIN Ambon, 2021)
Disabled family problem has been studied a lot so far, particularly family role in supporting the lives of family members with disabilities. However, aside from that, the other side of the lives of family members with disabilities needs to be studied, which is gender relation in disabled family life. This article studies the division of labor pattern of the disabled family based on the institutional and companionship families in Comongan District, Sukoharjo Regency, Central Java. There are two domains analyzed in this article. First, division of labor in domestic domain covering the fulfillment of food, clothing, and shelter needs, the decision making of children education, asset purchase, and health. Second, division of labor in public domain including economy, social, and religion. This article finds that the division of labor and the relationship pattern in disabled family are quite diverse. Some disabled families are able to build balanced relationship because they have independent life, either from financial perspective or from extended family intervension. Meanwhile, other disabled families still have less balanced patterns because their living conditions demand hard works or are not enough yet. The relationship built is not literally in accordance with the view of family relationship pattern in general. There are pattern modifications due to the disability experienced by disabled family members. Religious understanding participates in modifying the pattern and family relationship. Key words: division of work, relationship pattern, family, disabled